Awareness of Most Commonly Used Drugs in Dentistry Inducing Teratogenic Effects among Dental Practitioners - Ramani Priya1 , Krithika. C2 Gayathri.P.S 3 , Manju.J4 , Priyanka.p5 , Praveenkumar.S5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: The aim of the study was to assess the awareness of most commonly used drugs in dentistry inducing teratogenic effects, among dental practitioners. Birth defects may be caused by many factors such as physical conditions, teratogens, environmental exposures, genetic defects, etc., Although prescription drug use is common during pregnancy, the human teratogenic risks are undetermined for more than 90% drug treatments approved in the USA during the past decades. A particular birth defect may have its origins through multiple mechanisms and possible exposures including medications. A specific chemical process may result in different outcomes depending upon factors such as embryonic age at which a drug is administered, duration and dose of exposure and genetic susceptibility. Estimating the risk of fetal malformations attribute to the use of medications is difficult and perception of risk by health professionals will impact their counseling and treatment of patients. Pregnancy is a unique physiologic condition and importantly specific drugs like folic acid use may have several benefits for pregnant mother. The patient should maintain a good gynecologist patient-Dentist communication. For example a woman with two spontaneous abortions would be expected to be skeptical of any drug therapy in her next pregnancy and by communicating this to physicians and respective clinician. She may influence the physician and dentist perception. The clinician should be aware of all the newer drugs and its teratogenic effects. For health professionals this includes awareness of specific drug information and sources that provide realistic descriptions of risk beyond product monographs. A greater focus on this aspect may act to balance Risk perceptions. Physicians and dentists need to weigh risks and benefits of drug prescribing to pregnant patients based on the available knowledge.